2017
DOI: 10.1088/1742-6596/936/1/012002
|View full text |Cite
|
Sign up to set email alerts
|

Surface preparation effect on oxidation kinetics of Ni-base superalloy

Abstract: Abstract. In the present study an oxidation behavior of commercially available Ni-base superalloy IN 713C with different surface finishing, namely polished up to 1 μm diamond paste (resulting in R a =0.023) and ground by SiC paper with 80 grit (R a =1.23), were investigated at 950°C in air. It was found that ground sample developed very thin, protective α-Al 2 O 3 scale. Moreover, locally formation of θ-Al 2 O 3 in the forms of spikes was observed. For the sample with polished surface formation of outer chromi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…For materials used at elevated temperatures, their oxidation resistance and equally their lifetime at high temperatures become to be a crucial factor during materials engineering. It was found that different surface preparations result in a different oxidation behavior of a wide range of alloys, e.g., Ni-base superalloys [10][11][12][13][14][15], iron [16], or Fe-base alloys [17][18][19][20][21]. Surface preparation significantly influences the oxidation behavior of these materials.…”
Section: Introductionmentioning
confidence: 99%
“…For materials used at elevated temperatures, their oxidation resistance and equally their lifetime at high temperatures become to be a crucial factor during materials engineering. It was found that different surface preparations result in a different oxidation behavior of a wide range of alloys, e.g., Ni-base superalloys [10][11][12][13][14][15], iron [16], or Fe-base alloys [17][18][19][20][21]. Surface preparation significantly influences the oxidation behavior of these materials.…”
Section: Introductionmentioning
confidence: 99%
“…The exact mechanism responsible for such change is not known so far. However, it was proposed by Nowak et al [8] that during a different kind of surface preparation different amount/kind of defects are introduced into the near-surface region, namely, by the treatment resulting in higher surface roughness, a higher amount of defects are introduced. These defects are claimed to be easy diffusion paths of the elements forming protective oxide scales, as in the present case chromium.…”
Section: Discussionmentioning
confidence: 99%
“…Sudbrack et al investigated LDS-1101_HF and CMSX-4 with different surface conditions [7]. They observed strong a correlation between the surface preparation and type of formed oxide scale, namely, on ground surface, thin 2 [8]. It was found that chromium rich oxide formed on polished surfaces, while alumina oxide formed on ground surfaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also claimed, that not only temperature, but also amount of water vapor in the atmosphere has detrimental effect on the rate of volatilization of chromium species (Holcomb, 2008). It was also found by Nowak et al (2016) that the water vapour suppresses nitrides formation below the external chromia scale on Ni-base superalloy Rene 80. The authors correlated the latter with preferential adsorption of water vapor molecules on the surface and suppressing the nitrogen transport through the oxide scale.…”
Section: Introductionmentioning
confidence: 96%